2020
DOI: 10.5009/gnl18471
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Family History on Stage and Survival of Gastric Cancer According to the <i>TGFB1</i> C-509T Polymorphism in Korea

Abstract: Background/Aims: The survival rate of gastric cancer (GC) is known to be higher in patients with a family history (FH) of GC. There is an association between a polymorphism in the transforming growth factor-β1 (TGFB1) gene and the risk of GC in patients with first-degree relatives with GC. This study was performed to investigate whether a FH affects GC outcomes according to the TGFB1 C-509T polymorphism. Methods: TGFB1 was genotyped by the polymerase chain reaction-restriction fragment length polymorphism meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The HP infection status was determined by histologic examination with the Giemsa staining method, the rapid urease test (CLOtest, Delta West Ltd., Bentley, WA Australia) and/ or culture from the antrum and body, respectively, when GC was diagnosed by biopsy [21]. The diagnosis of GC was confirmed again histologically with removed surgical specimen.…”
Section: Hp Status Evaluationmentioning
confidence: 99%
“…The HP infection status was determined by histologic examination with the Giemsa staining method, the rapid urease test (CLOtest, Delta West Ltd., Bentley, WA Australia) and/ or culture from the antrum and body, respectively, when GC was diagnosed by biopsy [21]. The diagnosis of GC was confirmed again histologically with removed surgical specimen.…”
Section: Hp Status Evaluationmentioning
confidence: 99%
“…Single nucleotide polymorphisms related to cytokines such as transforming growth factor-β1 and interleukin-1 have been investigated to establish genetic predisposition in GC patients with FH [14,15]. Additionally, GC patients with FH present a lower cancer stage (I-II) at diagnosis than those without FH, but overall survival was not different between patients with and without FH [16].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies are about the mutations, variants, and polymorphisms of TGFB1 with gastric cancer. For example, the C-509T [ 38 ] and 509C/T [ 39 ] mutations were significantly associated with gastric cancer invasion. Therefore, in this study, by performing bioinformatics analysis, we showed that TGFB1 could also be considered as a diagnostic biomarker for gastric cancer.…”
Section: Discussionmentioning
confidence: 99%